PENGARUH MODAL INTELEKTUAL TERHADAP KINERJA KEUANGAN PERUSAHAAN (STUDI EMPIRIS PADA BURSA EFEK INDONESIA) - Herawati, Helmi (JURNAL EKOMBIS REVIEW, 2017)
Helmi Herawati; The study of intellectual capital in Indonesia originated from the emergence of PSAK No.19 which was the beginning of the development of intellectual capital. PSAK No.19. The data to be used in this study is all companies listing on the BEI using annual financial statements obtained with online database http://www.idx.co.id/. The amount of sample is as many as 397 companies listing on BEI, using the technique of sampling sampling is a type of random sample selection of information obtained by using certain considerations or with the aim to obtain a representative sample in accordance with the criteria specified. Based on the results of testing with PLS note that IC (VAIC) does not positively affect the financial performance of the company. Hence, therefore, H1 is not acceptable. From the result of PLS testing indicates that IC (VAIC) positively has no effect on future company's financial performance. Hence it means that H2 is not proven. From the result of testing of PLS present proof that there is no positive influence of ROGIC to financial performance. From result of PLS test show that IC contribution to a future performance of company there is no difference according to type of company sector. So that means H4 is rejected.ey Words: Intangible Assets, Intellectual Capital, Corporate Financial Performance.